Lutto, silenzi e omissioni: la 'Vita nova' fra vissuto e poetato (Quaderni di Gargnano, 2022)
This essay reflects on Dante's exploration of the theme of mourning in the Vita nova. It draws on critical approaches proposed by Giorgio Agamben, on the challenges of concluding poetic works, and by Nicola Gardini, on the eloquence of the unsaid, to review how Dante's organization of a unified narrative text still leaves space for inarticulacy, silences and omissions that together underline the difficulty of voicing sorrow in poetic form. As the ending of the Vita nova projects Dante's "book of memory" forward towards future as well as past experiences, biographical and poetic, his poetics of mourning for Beatrice become closely imbricated with the eloquence of what is not (yet) uttered.Questo saggio riflette sull'esplorazione dantesca del tema del lutto nella Vita nova. Attingendo agli approcci critici proposti da un lato da Giorgio Agamben, sulle difficoltà di concludere un'opera poetica, e dall'altro da Nicola Gardini, sull'eloquenza del non detto, esso esamina come l'organizzazione dantesca di un testo narrativo unitario lasci ancora spazio all'inarticolazione, ai silenzi e alle omissioni, che insieme sottolineano la difficoltà di dare voce al dolore in forma poetica. Poiché il finale della Vita nova proietta il "libro della memoria" di Dante verso esperienze passate e future, biografiche e poetiche, la sua poetica del lutto per la morte di Beatrice si lega strettamente alla retorica del non (ancora) detto.
Keywords: Dante; Vita nova; lutto; mourning; lacuna; Giorgio Agamben; Nicola Gardini